2014
DOI: 10.1037/a0036295
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition and psychopathology: A meta-analysis of go/no-go task performance.

Abstract: Response inhibition, defined as the ability to withhold a response, is considered to be a core deficit in various mental illnesses. Measures of response inhibition have been used to define functional deficits, as markers of genetic risk, in neuroimaging studies, and for diagnostic purposes in these disorders. However, the magnitude of the deficit across psychopathologies has not been systematically assessed. We conducted a systematic review and meta-analysis of performance on commonly used measures of the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
209
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(233 citation statements)
references
References 86 publications
(129 reference statements)
21
209
2
1
Order By: Relevance
“…However, this deficit might be subtle given that the accuracy levels in the no-go trials were not associated with SR scores. Although this lack of association between reward sensitivity and No-go accuracy is contrary to what we expected, a recent meta-analysis has shown that omission errors, rather than commission errors, characterize the performance pattern of several psychopathologies, including ADHD, autism, bipolar disorder, personality disorder, reading disorder and schizophrenia (Wright, Lipszyc, Dupuis, Thayapararajah, & Schachar, 2014). This deficit is not specific of any disorder, but is a shared feature that may reflect lapses in focused attention.…”
Section: Reward Sensitivity and Behavior In The Go/no-go Taskcontrasting
confidence: 53%
“…However, this deficit might be subtle given that the accuracy levels in the no-go trials were not associated with SR scores. Although this lack of association between reward sensitivity and No-go accuracy is contrary to what we expected, a recent meta-analysis has shown that omission errors, rather than commission errors, characterize the performance pattern of several psychopathologies, including ADHD, autism, bipolar disorder, personality disorder, reading disorder and schizophrenia (Wright, Lipszyc, Dupuis, Thayapararajah, & Schachar, 2014). This deficit is not specific of any disorder, but is a shared feature that may reflect lapses in focused attention.…”
Section: Reward Sensitivity and Behavior In The Go/no-go Taskcontrasting
confidence: 53%
“…Given that other parts of the world have different legal drinking ages and the suggestion that underage illegal drinking may be more strongly associated with impulsivity than legal drinking, it is important to mention that all participants in the current study were of legal drinking age for this province/country. The Go/No-Go task is a well-established fMRI compatible measure of response inhibition in which participants are initially required to respond to a stimulus, thus creating a strong cued tendency to respond, which is followed by withholding response to the conditioned stimulus (Wright et al, 2014). In healthy adult controls, the Go/No-Go task has been shown to be dependent on activation of the anterior cingulate, dorsolateral prefrontal cortex, inferior frontal cortex, inferior parietal lobule, premotor cortex, thalamus, and the caudate using fMRI (Dosenbach et al, 2008;Longo et al, 2013;Stevens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, response inhibition could be conceptualised as the process of not attenuating to a strongly conditioned cue (Wright et al 2014). Poor response inhibition performance, often referred to as 'behavioural disinhibition', demonstrates an inability to restrain a response that is no longer adaptive, or at least no longer appropriate (Strakowski et al 2009;Winstanley et al 2006).…”
Section: Understanding Within-session Loss Of Cognitive Controlmentioning
confidence: 99%
“…Response inhibition performance was recorded via a modified version of the classical go/ no-go task (Fillmore 2003), which is a measure of ability to withhold a prepotent response as well as attention, vigilance and reaction time (Wright et al 2014). Participants were presented with directional arrows, pointing either left or right, on a computer screen, for a period of 1500 ms, with each arrow cued by a fixation point for a duration of 500 ms.…”
Section: Go/no-go Taskmentioning
confidence: 99%
See 1 more Smart Citation